AN ANALYSIS OF COOPERATIVE PRINCIPLE MAXIM VIOLATIONS IN THE 'WHY OPPOSITION IS IMPORTANT?' EPISODE OF THE BASED INDONESIAN TALKS PODCAST - Putri Annisa Zulhantiar; Aisyah Inka Putri Lubis; Jamaluddin Nasution (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study investigates the interplay between Conversation Analysis (CA) and Gricean maxims in the Based Indonesian Talks podcast episode “Why Opposition is Important?”. Eight excerpts were analyzed to examine how conversational structure and pragmatic strategies shape political discourse between the hosts, Panji Pragiwaksono and Andriy. The results show that 24 violations of Grice’s Cooperative Principle occurred throughout the episode, with the Maxim of Quantity being the most frequently violated (33.33%), followed by Relation, Quality, and Manner. CA findings reveal that these violations consistently align with identifiable interactional patterns, including extended turns, dispreferred responses, humor sequences, metaphorical statements, and minimal repair. Rather than indicating communicative breakdown, the maxim violations function as strategic resources that enhance persuasion, maintain humor, manage ideological contrast, and enable indirect political critique. The study concludes that pragmatic flexibility supported by orderly turn-taking and sequence organization allows speakers to address sensitive political issues while preserving conversational cooperation. This integrated CA–Grice approach provides deeper insight into how political commentary is constructed in informal podcast discourse.